Does the resistance to glyphosate herbicide affect the competitive ability of ryegrass with soybean? - Oliveira,C. (2014)
The objective this work was to investigate the competitive ability between resistant and susceptible ryegrass biotypes and of these with soybean crop. Four experiments were carried under greenhouse, in a completely randomized design with four replications, in 2011 and 2012. Treatments were arranged in additive series and replacement series assay. In each series, the proportions among ryegrass resistant and susceptible plants related to soybean were: 100:0, 75:25, 50:50, 25:75 e 0:100. Leaf area and shoot dry mass were evaluated. Competitiveness statistical analysis consisted in applying diagrams to the replacement series and alternative interpretations of the competitiveness indexes. The soybean crop had equivalent competitiveness to the susceptible ryegrass biotype and inferior to the resistant biotype, while the biotypes, both susceptible and resistant to glyphosate, present equivalent competitive ability. In general, the intraspecific competition is more harmful to ryegrass when in competition with soybean, while interspecific competition is predominant for culture.